2011 IEEE GLOBECOM Workshops (GC Wkshps) 2011
DOI: 10.1109/glocomw.2011.6162585
|View full text |Cite
|
Sign up to set email alerts
|

Creation of degraded wiretap channel through deliberate noise in block ciphered systems

Abstract: In this paper we propose an encoding-encryption approach to take advantage of intentional noise introduced in ciphertexts for DES based block ciphers working in CFB mode. Despite Eve's efforts in modifying her linear crytanalysis given the intercepted noisy ciphertexts, there is still a non-negligible probability of having either a crypto-analysis failure or a misdetected key under her limited resources. Consequently, we essentially create a wiretap channel in application layer that is a degraded version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As a result, the total number of 56 key bits examined in linear attack with bit advantage is . In [21], A. Selçuk showed that when the total number of gathered plaintext/ciphertext pairs is large enough, the probability of success , defined as the probability that the right key is among top candidates, can be derived as (1) where is the bit advantage of the attack, is the bias of the used linear approximation and is the cumulative distribution function of the standardized normal distribution.…”
Section: B Linear Cryptanalysismentioning
confidence: 99%
“…As a result, the total number of 56 key bits examined in linear attack with bit advantage is . In [21], A. Selçuk showed that when the total number of gathered plaintext/ciphertext pairs is large enough, the probability of success , defined as the probability that the right key is among top candidates, can be derived as (1) where is the bit advantage of the attack, is the bias of the used linear approximation and is the cumulative distribution function of the standardized normal distribution.…”
Section: B Linear Cryptanalysismentioning
confidence: 99%
“…This gives more insight on the security application of electronic commerce. Researchers began to consider replacing DES with AES (Daemen and Rijmen, 1998;Khiabani and Shuangqing, 2011) for a high security margin. However, in the most recent result about AES, Rijndael has been theoretical broken by Bogdanov et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is almost never the case in wireless communications, where the signals received by the eavesdropper is always corrupted by interference/noise. In fact, recent works indicate that certain stream ciphers are less vulnerable to known attacks if the cipher text is corrupted by noise [3]. By comparison, the physical layer, i.e., information theoretic security, approach does take into account of the benefit of a noisy channel for secrecy [2].…”
Section: Introductionmentioning
confidence: 99%